Виховний потенціал студентських блогів - Варенко, Т.К. (КПУ, 2016)
У статті розглядається виховний потенціал ведення студентами блогів академічних груп у рамках навчально-педагогічного процесу, обґрунтовується ефективність впровадження такої практики у навчально-виховний процес у вищій школі. Експериментально встановлено, що студентський колективний блогінг, координований викладачем і тематикою навчальної програми, сприяє розвитку у студентів уміння вести діалог з усіма учасниками дискусії, керуючись принципами толерантності і враховуючи загальноприйняті норми поведінки. У студентів, які спільно ведуть блог групи, підвищується рівень самоорганізації і самодисципліни, зростає самооцінка і впевненість у собі, культивується відповідальне і шанобливе ставлення до оточуючих і самих себе, формуються навички використання сучасних інформаційних і комунікаційних технологій. Більше того, практика блогінгу дозволяє мінімізувати випадки академічного плагіату і надає студентам унікальний емоційно-ціннісний досвід спілкування. / Varenko T. K. Character-Building Potential of Student Blogs. The article provides an insight into the character-building potential of engaging students in collective blogging within the educational-pedagogical process. It substantiates the efficiency of such practice implementation in the higher education environment. The analysis of the experimentally received data gives grounds to conclude that student group blogging, when coordinated by the instructor and the curriculum, contributes to developing the students’ ability to establish and maintain a dialog with all the participants of the discussion relying on the principles of tolerance and with regard to the generally accepted norms of conduct. Educational group blogging boosts students’ self-appraisal and self-reliance, hones their self-organization and self-discipline skills, cultivates responsible and respectful attitude to others and themselves, and develops their ability to utilize modern information and communication technologies. Group blogging is an excellent tool in applying the individual approach offering the student bloggers freedom to choose what to write about and how to present it. When blogging for the real readers (groupmates and potentially anyone from all over the world who comes across their blog on the web) rather than their instructor only, students tend to be more creative, honest and enthusiastic in expressing themselves, no longer treating the assignment as a pure formality. Moreover, blogging helps dwindle academic plagiarism and is a unique emotional and value-based communication experience for students. Besides, this practice contributes to harmonious integration of education and character-building, which complies with the main provisions and principles of the effective legislation of Ukraine in education. Key words: blogging, character-building potential, creative self-fulfillment, dialogical relations, student blog.
Keywords: блогінг; виховний потенціал; діалогічні відносини; студентський блог; творче вдосконалення